Developing Indonesia Sign Language (BISINDO) Application with Android Based for Learning Sign Language - Shinta Adhya Nurpiena; Endar Suprih Wihidayat; Aris Budianto (Journal of Informatics and Vocational Education, 2021)
Problems that occur in learning Indonesian sign language, especially for the Solo area, are the scarcity of opening sign language classes for the public and the limited use of instructional media. To overcome this problem, an Android-based sign language learning media application was developed with the ADDIE research method. ADDIE method, namely analysis, design, development, implementation and evaluation. This research will focus on the feasibility test of the application of learning media by using the indicators on the ISO 25010, standard that is used to test the feasibility of the software. The aspects tested are functional suitability, usability aspects, portability aspects and validation by material experts and media experts. The results of the feasibility test obtained, for the functional suitability test 100%, usability test 83.2%, 100% portability test, 100% material expert test and 93% media expert and it can be concluded that the application of sign language learning media is feasible to use.